Facilitating critical thinking using the C-QRAC collaboration script: Enhancing science reading literacy in a computer-supported collaborative learning environment. (October 2015) - Lee, Yuan-Hsuan
Abstract: The criticism that reading online results in shallow reading may reflect the need for an intervention that can provide sufficient technological and pedagogical supports to socially and cognitively engage learners in critical thinking and collaboration. This study investigated the effect of facilitating critical thinking using a collaboration script modified from the Questioning, Reading, Answering, and Checking reading strategy (i.e., QRAC-the-Code; Berkeley & Riccomini, 2013) on students' science reading literacy in a computer-supported collaborative learning (CSCL) environment. Participants were 76 college students (71% female) enrolled at a university in central Taiwan. Students were grouped by affinity grouping, where they self-selected their members, and were then randomly assigned to a collaborative learning condition with or without the collaboration script support. Overall, results showed that the collaboration script significantly enhanced students' reading literacy. Moreover, the effect was dependent upon gender and the format of tests. Males benefited more from the collaboration script on constructed-response items whereas females benefited more on multiple-choice items. Implications for instructional practices are drawn based on the findings of the study. Highlights: Critical thinking in reading was encouraged with or without CQRAC script support. The CQRAC group outperformed the control group in reading literacy. The result was dependent on the gender moderation and test format. The CQRAC script benefited males more in constructed-response items. The CQRAC script benefited females more in multiple-choice items.